A criatividade na fala do professor de física - Danilo Ribeiro Sa Fortes (2003)
This research investigates the creative work of five peculiar Physics teachers from E.E.Gov.Milton Campos high school in Belo Horizonte, set up from semi-structured, recorded and transcribed interview. The analysis was proceeded by using theoretical parameters of professional cycles defined by Huberman et al (1993) and design-like tasks defined by Schön (2000). The categories of analysis stemmed from the construction of an analytical frame of the concept of creativity set by Rhodes (1961) and included the point of view of the tetrahedron of principles derived from Vaz (1989) about pedagogical, sociological and psychological aspects of his teaching professionalism. We hope to identify the characteristics of creativity in teachers considered as creative by the high school community where they belong to and as a consequence to establish relations between the teaching praxis and the teaching knowing of these educators. As result, we intend to find markers for the creative individual and the manufacturing process of his/her work.